2010
DOI: 10.1002/cplx.20336
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal, and modulatory factors affecting GasNet evolvability in a visually guided robotics task

Abstract: Spatial, temporal, and modulatory factors affecting the evolvability of GasNets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Both these extended forms proved to be significantly more evolvable again than the basic GasNet. Other varieties include nonspatial GasNets where the diffusion process is replaced by explicit gas connections with complex dynamics (Vargas et al 2009) and version with other forms of modulation and diffusion (Husbands et al 2010). In order to gain insight into the enhanced evolvability of GasNets, detailed comparative studies of these variants with each other, and with other forms of ANN, were performed using the robot task illustrated in Figure 3 ( Philippides et al 2005b.…”
Section: Volume Signalling: Gasnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these extended forms proved to be significantly more evolvable again than the basic GasNet. Other varieties include nonspatial GasNets where the diffusion process is replaced by explicit gas connections with complex dynamics (Vargas et al 2009) and version with other forms of modulation and diffusion (Husbands et al 2010). In order to gain insight into the enhanced evolvability of GasNets, detailed comparative studies of these variants with each other, and with other forms of ANN, were performed using the robot task illustrated in Figure 3 ( Philippides et al 2005b.…”
Section: Volume Signalling: Gasnetsmentioning
confidence: 99%
“…Four of the nodes are assigned as motor nodes (forward and backward nodes for the left and right motor, with motor speeds proportional to the output of the relevant forward node minus the output of the relevant backward node). See Husbands et al (1998Husbands et al ( , 2010 for full details.…”
Section: Flatenmentioning
confidence: 99%
“…The next two articles consider the effects of spatial embedding on artificial and biological neural networks. Husbands et al [23] explore the influence of spatial and temporal constraints on a class of artificial neural networks known as GasNets, that incorporate two interacting signaling mechanisms: one based on electrical connections, the other on a diffusible gaseous neurotransmitter. Their findings indicate that spatial embedding facilitates exploitation of loose coupling between these signaling mechanisms in a way that enhances evolvability.…”
Section: Contents Of This Special Issuementioning
confidence: 99%
“…This, combined with insights from evolutionary robotics (Nolfi et al, 2016;Vargas et al, 2014) where it was discovered that dynamically complex neural networks are highly evolvable (Husbands et al,2 Evolutionary Computation Volume x, Number x 2010; Beer and Williams, 2015), suggested that analog EHW might be very well suited to evolving compact controllers operating with small numbers of components, even for visually guided behaviours which traditionally employed high levels of processing (Bekey, 2005). An interesting property of the dynamically complex evolved networks mentioned above is their ability to cope with noisy, poor quality sensory data, even when the networks have very few nodes (Husbands et al, 2010). This suggests that analog EHW might also be a useful approach for low cost realtime hardware applications requiring cheap sensors and simple circuits.…”
Section: Introductionmentioning
confidence: 99%